Registry Errors in the Cadastre under Modern Conditions - N. A. Bondareva (Учёт. Анализ. Аудит)
The introduction of new legislation to determine the cadastral value of property calls for solution of some problems. Poor cadastral valuation leads to errors in the activity of a cadastral engineer. In particular, the lack of developed methodological support, speeding up the training of cadastral valuation staff, unreliability or lack of cadastral information in most areas of the country, obsolete equipment, the lack of R & D and the application of the method of mass valuation of real estate, which does not take into account the individual characteristics of the object of valuation, can result in registry errors. The considered direction of the state registration of the land fund is at the very beginning of its development, which will require the further adjustment of the legislation, new approaches to training and certification of cadastral engineers and organization of their activity. To this end, the article analyses the types of allowed registry errors, their classification, as well as the legislation determining responsibility for such errors. As the mistakes made by a cadastral engineer influence economic activity of organizations, expenses of regions, the author offers classification of register errors based on the principle of materiality.